MOTIVASI SANTRI DALAM MELAKSANAKAN RIYADAH QUR’AN 41 HARI : Isna Annisa Permatasari - Isna Annisa Permatasari (ISLAMIDA Journal of Islamic Studies, 2022)
Abstract The research background is based on the anxiety of researchers about bad morals that are still often occur around us. This is due to the lack of motivation regarding the formation of good morals.To grow one's awareness, of course, there needs to be a revamping process that is done early on. In this case, Pondok Pesantren Bustanu Usysyaqil Qur'an implements various practices, one of which is in the form of Qur'anic riyadah which is done every day for 41 consecutive days by fasting and matching the Qur'an. The study aims to know about the motivation of santri in carrying out the Qur'anic riyadah 41 days and how it has implications for their daily morals. This research is a qualitative study with the background of Pondok Pesantren Bustanu Usysyaqil Qur'an Gading, Duren, Tengaran, Semarang Regency. The subjects were the caretaker of Pondok Pesantren and santri riyadah Qur'an. Data collection is from observations, interviews, and documentation. In the data validity test, the author uses data triangulation by comparing information obtained from several different sources and different techniques. Then data analysis is done using miles and huberman models, data reduction, data supply, and inference conclusions.The results showed that: (1) Santri motivation in carrying out the Qur'anic riyadah 41 days varies but is generally grouped into two, namely motivation that comes from a person (internal) and motivation that comes due to external stimulation, namely encouragement from Nyai, parents, and alumni.(2) The motivational implication of santri's daily morals is to make his heart trained to be patient, tawadu', istiqomah, discipline, qana'ah and as form of birrul walidain.The implications felt by santri in this case vary depending on each individual in interpreting the Qur'anic riyadah, but in general riyadah Qur'an 41 days has a power impact in memorizing and forming good morals (Akhlaqul karimah) because riyadah basically includes about moral education and treatment of bad morals.